2020
DOI: 10.1021/acs.est.9b07429
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on the Direct Photolysis of Benzotrifluoride Derivatives

Abstract: The chemical class of benzotrifluoride derivatives is widely used in active ingredients of various commercial products, such as pharmaceuticals, pesticides, herbicides, and crop protection agents. Past studies have shown that some benzotrifluorides are not stable under UV irradiation in water and convert into benzoic acids due to C–F bond hydrolysis. It was also observed, but never systematically studied, that the ring substituents play an important role on the direct photochemical reactivity of the CF3 moiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Identification of fluorinated reaction products from photolysis processes has only received limited attention. Thus, fluorinated products formed via degradation of these compounds may pose unforeseen consequences such as production of benzoic acids via the photolysis of trifluoro­methylphenyl dervatives . To better understand the degradation pathways of these fluorinated compounds in the environment, reliable detection methods must first be established.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of fluorinated reaction products from photolysis processes has only received limited attention. Thus, fluorinated products formed via degradation of these compounds may pose unforeseen consequences such as production of benzoic acids via the photolysis of trifluoro­methylphenyl dervatives . To better understand the degradation pathways of these fluorinated compounds in the environment, reliable detection methods must first be established.…”
Section: Introductionmentioning
confidence: 99%
“…Manfrin et al (2020) studied how the substituents on the benzene ring could change the rates of direct photodefluorination for benzotrifluorides, which can be considered a SAR study for our purpose. 14 This transformation is described by the "trifluoromethyl photohydrolysis" reaction scheme in our reaction library. This study found that monosubstituted benzotrifluorides bearing an electron-donating group such as −OH, −NHMe, and −NH 2 on the ring enhanced photohydrolysis, while the ones bearing an electronwithdrawing group show lower photoactivity for the compounds they investigated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Below, we provide a back-of-the-envelope example of how (Q)­SAR development could help improve the reaction library. Manfrin et al (2020) studied how the substituents on the benzene ring could change the rates of direct photodefluorination for benzotrifluorides, which can be considered a SAR study for our purpose . This transformation is described by the “trifluoromethyl photohydrolysis” reaction scheme in our reaction library.…”
Section: Resultsmentioning
confidence: 99%
“…While oxidative defluorination has been demonstrated previously ( 29 , 73 , 74 ), the mechanism of defluorination of 4-fluorobenzotrifluoride was not immediately obvious. Moreover, the trifluoromethylphenyl moiety has become common in drugs and agricultural chemicals, with the goal of increasing effective lifetime by inhibiting microbial degradation ( 9 , 75 ). 4-Fluorobenzotrifluoride underwent only partial transformation via the toluene biodegradative (Tod) pathway, and this was the key to the large extent of defluorination observed.…”
Section: Discussionmentioning
confidence: 99%